2012
DOI: 10.1016/j.foodres.2011.09.016
|View full text |Cite
|
Sign up to set email alerts
|

Features and performance of edible films, obtained from whey protein isolate formulated with antimicrobial compounds

Abstract: The goal of this research effort was to assess the efficacy of edible films produced from whey protein isolate (WPI) and glycerol, including incorporation of lactic acid (LA) and propionic acid (PRO), chitooligosaccharides with nominal MW of 3 kDa (COS) and natamycin (NA) as antimicrobial agents. Their features were evaluated in vitro via agar diffusion and viable cell counting, against spoilage microflora often found contaminating cheese surfaces. The effect of incorporating the aforementioned compounds upon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
61
2
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(79 citation statements)
references
References 59 publications
9
61
2
7
Order By: Relevance
“…Mean values and standard deviations were calculated from the experimental data. The Statistical Package for Social Sciences (SPSS), v. 17.0 (Chicago, IL, USA) was used in view of its superior performance in previous related work within our group (Madureira, Amorim, Gomes, Pintado, & Malcata, 2011;Ramos et al, 2011b). ShapiroeWilk normality tests were applied to the difference of means between pairs; however, most datasets were not found to satisfy the homoscedasticity hypothesis.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Mean values and standard deviations were calculated from the experimental data. The Statistical Package for Social Sciences (SPSS), v. 17.0 (Chicago, IL, USA) was used in view of its superior performance in previous related work within our group (Madureira, Amorim, Gomes, Pintado, & Malcata, 2011;Ramos et al, 2011b). ShapiroeWilk normality tests were applied to the difference of means between pairs; however, most datasets were not found to satisfy the homoscedasticity hypothesis.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Los valores de espesor se encontraron en el rango 0,03 a 0,1 mm, valores que son similares a los reportados por Zhong y Xia (2008); ellos reportaron valores promedios de espesor de 0,100 ± 0,017 mm en películas compuestas de quitosano, almidón de yuca y gelatina, utilizando glicerol como plastificante. Por otra parte, Ramos et al (2012) reportaron valores de espesor en películas, formuladas a base de aislado de proteína de suero de leche, de 0,13 ± 0,01 a 0,19 ± 0,04 mm. Es de esperarse que los espesores de películas aumenten al aumentar la concentración de soluto, si el área de formación es contante; característica que dependerá también del soluto para formar la película y de los ingredientes adicionados para crear algún cambio, ya sea fisicoquímico o con alguna intención para la mejora del alimento que será recubierto con la película.…”
Section: Resultados Y Discusión Espesorunclassified
“…Posteriormente, se midieron los valores de absorbancia a 600 nm. El valor de transparencia fue calculado utilizando la siguiente ecuación (Ramos et al, 2012).…”
Section: Transparenciaunclassified
“…Oll e Resa et al (2013), studied a tapioca starch based film containing natamycin and observed that the preservative was available to prevent an external contamination of S. cerevisiae and that the antimycotic effect exerted by the films depended on the natamycin content. Also Ramos et al (2012) studied the efficacy of films produced from whey protein isolate containing natamycin as antimicrobial agent and observed that the natamycin incorporated in the film led Y. lipolytica to depletion within 3 h of storage at 30 C.…”
Section: Effectiveness Of Film Nani Acting As Barrier To Mixed Culturmentioning
confidence: 99%
“…Several authors developed biopolymeric matrices containing nisin or natamycin (Basch, Jagus, & Flores, 2013;Cao-Hoang, Chaine, Gr egoire, & Wach e, 2010;Fajardo et al, 2010;Oll e Resa et al, 2013;Ramos et al, 2012;Ture et al, 2011). However, scarce data (Oll e Resa et al, 2014a;Oll e Resa et al, 2014b) exists in relation to the activity of these natural antimicrobials incorporated together in these matrices and used in real foods against a mixed culture.…”
Section: Introductionmentioning
confidence: 99%